COMPARATIVE STUDY OF THE NUTRITIONAL AND MICROBIAL SAFETY OF FRESH “WARA” HAWKED IN ILORIN AND OGBOMOSO TOWNS - Oyeyinka, Samson Adeoye (Journal of Agricultural Sciences (Belgrade), 2018)
Malnutrition resulting from low protein intake is one of the nutritional problems facing most developing countries including Nigeria. Most proteineous food sources are costly and in short supply. “Wara” is a proteineous ready to eat food product made by curdling milk. It does not normally undergo any further safety treatment before consumption. Frequent hawking on our major streets and roads call for determination of the safety of these products. Wara samples sourced from four different locations each at Ilorin, Kwara State and Ogbomoso, Oyo State respectively, were analysed for nutritional and microbial safety. Proximate composition of the samples over the period of storage showed that moisture content and carbohydrate increased from 59.69-72.00% and 2.39-11.39% respectively, while protein, fat and ash contents reduced from 22.20-10.80%, 15.80-3.62% and 2.99-0.25% respectively. Microbial and fungal counts ranged from 2.0 X 102 cfu to 6.3 X 105 cfu and 2.0 X 102 cfu to 7.1 X 105 cfu respectively. Klebsiella and salmonella species, Escherichia coli and some fungi were isolated. The study revealed that some of the hawked cheeses are not safe for consumption. Attributable reasons being unhygienic practices of the hawkers or producers and/or lack of requisite preservative.